Structural analysis of a series of copper(II) coordination compounds and correlation with their magnetic properties - Kozlevčar, Bojan (Array, 2008)
Abstract: The chemistry of copper(II) is widely described in the literature due to its importance in various fields of research and because of the relative ease in the synthesis of new compounds. The magnetochemistry is one of these fields. However the results obtained with 'the magnetic methods' e. g. EPR and magnetic susceptibility, that may enable important insight in the properties of the compounds, are very often ambiguous. The structural correlation of the wide range of copper(II) complexes with the magnetic analysis can fulfil some gaps in this area. A series of copper(II) complexes, synthesized in our lab during the last decade, is discussed